Bali Bridal Makeup As Cultural Wisdom in 4.0 Era - Mutimmatul Faidah; Ni Luh Ayu Astiti; Ni Putu Delia Wulansari (Jurusan Sastra Indonesia, 2020)
This study aims to describe the influence of caste on Balinese bridal make-up and explain a cultural wisdom on bridal make-up in Industrial Revolution 4.0. This research is a qualitative. Ethnography theory was used to analyze the data. There are three Balinese makeup styles, Madya Balinese Bridal Make-up for Weisa and Kstaria castes, Nista Bridal Make-up for the Sudra caste and Bali Agung Payas Bride for the aristocracy. Bridal make up is a medium of communication for Balinese culture.